Penerapan Sistem Informasi Geografis dalam Penentuan Jarak Zonasi Sekolah Menengah Pertama (SMP) dalam PPDB Melalui Jalur Zonasi/Domisili (Studi Kasus: Kota Semarang) - Aurellia Callista Dewi; Bambang Agus Herlambang; Ahmad Khoirul Anam (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The implementation of the zoning-based admission policy (PPDB) in Semarang City continues to face challenges related to the accuracy of distance measurement and the transparency of information provided to the public. This study aims to examine the application of Geographic Information Systems (GIS) in defining zoning boundaries for public junior high schools in Semarang City and integrating the results into a web-based information platform. A quantitative descriptive approach was employed, incorporating spatial analysis through a 3-kilometer buffer radius using QGIS software. The results indicate that buffer analysis is effective in delineating priority domicile zones based on school coordinate data. These findings are integrated into a GIS-based website that presents visual information on school locations, enrollment capacity, and final score calculation mechanisms in accordance with current regulations. The proposed system contributes to improving information transparency, enabling the public to better understand admission opportunities while supporting government decision-making in promoting equitable access to education. For future development, the use of road network analysis is recommended to obtain more realistic distance estimations.